About the International Conference “Manuscript of Lithuanian Tatars — National Treasure (dedicated to the 100th Anniversary of the Discovery of the Kitab of Ivan Lutskevich)” - Girniuvienė, Tatjana (Slavistica Vilnensis, 2016)
...